BDNF and memory processing - Bekinschtein, Pedro Alejandro (2014)
Brain-derived neurotrophic factor has emerged as one of the most important molecules involved in memory. Its wide role in different types of memories that depend on different structures as well as its involvement in distinct memory stages points at BDNF as one likely target to treat cognitive impairments and anxiety-related memory disorders. However, regulation of BDNF expression is very complex as well as its modes of action. Here we describe the latest research carried out on the function of BDNF in memory to illustrate such complexity.